2012
DOI: 10.1111/anec.12005
|View full text |Cite
|
Sign up to set email alerts
|

Indexes of Temporal Myocardial Repolarization Dispersion and Sudden Cardiac Death in Heart Failure: Any Difference?

Abstract: Our data show that variability in the first (QTpeak VI) and second halves of the QT interval (Tpeak -Tend VI) significantly contributes to the QTend VI in patients with CHF. Further studies should investigate whether these indexes might help stratify the risk of SCD in patients with a moderately depressed LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 40 publications
(66 reference statements)
3
47
0
Order By: Relevance
“…42 Experimental and clinical evidence show that this repolarization phase is closely linked to sympathetic activity. 14,15,43,44 The small, though significant, positive relation we found between T e VI and the SGNA/VNA ratio could therefore support its usefulness, since we showed that after MI, notwithstanding a preserved left ventricular ejection fraction, this terminal repolarization phase worsens owing to the increased sympathetic and reduced vagal activity or to both events. Conversely, the same terminal repolarization phase, under baseline conditions, seems unrelated to dispersion owing to the increased SGNA/VNA ratio.…”
Section: Discussionmentioning
confidence: 56%
“…42 Experimental and clinical evidence show that this repolarization phase is closely linked to sympathetic activity. 14,15,43,44 The small, though significant, positive relation we found between T e VI and the SGNA/VNA ratio could therefore support its usefulness, since we showed that after MI, notwithstanding a preserved left ventricular ejection fraction, this terminal repolarization phase worsens owing to the increased sympathetic and reduced vagal activity or to both events. Conversely, the same terminal repolarization phase, under baseline conditions, seems unrelated to dispersion owing to the increased SGNA/VNA ratio.…”
Section: Discussionmentioning
confidence: 56%
“…While various metrics [e.g., SDQT (27), normalized QTV (24), QTV index (10), short-term variability ratio (37), peakto-end of T wave interval variability (44)] have been proposed to quantify beat-to-beat repolarization variability, the association of individual measures with future adverse events has been inconsistent among studies (24,41,50). Nevertheless, SDQT has been shown to correlate significantly with normalized QTV and the QTV index in HF patients (41).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Albeit controversial [17,27,28,29,30], an increase in both spatial and temporal QT subsegment dispersion is thought to represent a useful noninvasive marker of arrhythmic risk in patients with congestive heart failure and in other disease settings [9,12,13,22,23,31,32]. Conversely, whether the QT dispersion might be an additive marker in identifying HCM patients with an increased arrhythmia propensity represents a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of clinical variables, such as distribution and magnitude of ventricular hypertrophy and fibrosis, as well as LV dysfunction, might potentially alter this ECG-derived parameter, thus limiting its use in routine clinical practice [7,8,9,10,11]. Recently, it has been suggested that the T peak -T end interval (T p T e ) may be a surrogate for transmural dispersion of repolarization and T p T e may be a more sensitive index of the dispersion of ventricular repolarization than the whole QT e or the Q-T peak interval (QT p ), given it closely reflects the termination of repolarization in the 3 myocardial cell layers [16,17,18]. In this context, the relationship between each of the QT segment dispersions and ventricular arrhythmias is an aspect not yet systematically investigated in HCM.…”
Section: Introductionmentioning
confidence: 99%